Benefits of using TiO2 quantum dots in producing low-cost and high-quality white light-emitting diodes - Phuc Dang Huu; Phung Ton That; Tran Thanh Trang; Phan Xuan Le; Nguyen Doan Quoc Anh (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2022)
Quantum dots (QDs) is considered as a potential material for the improvement of light-emitting diodes (LEDs). However, different from the traditional phosphor materials, they have unique scattering and absorption properties affected by their several nanometers sizes, which makes their application in the production of LED confront more challenges. In addition to this, their influences on QDs-converted LEDs (QCLEDs) are rarely investigated. So as to propose solutions for those problems, in this article, we experimentally and theoretically investigated the impacts of titanium dioxide (TiO2)QDs’ scattering and absorption on the light quality of QCLEDs by drawing a thorough comparison between their properties and the traditional yttrium aluminum garnet phosphors characteristics. The outcomes showed that QCLEDs have poor radiant efficacy and stability due to QDs’ strong characteristic of absorption (reabsorption) while their weak scattering property causes a low uniformity in correlated color temperature (CCT). For achieving high efficiency and stability white LEDs, we highly suggest using QDs with a low concentration to get reductions in the reabsorption and total internal reflection losses. With 0.05 concentration of TiO2 nanoparticles (TiO2 NPs), the white LEDs can simultaneously achieve a high CCT (approximately 7500 K) and a high color rendering index (around 85).